2022
DOI: 10.3923/pjbs.2022.867.874
|View full text |Cite
|
Sign up to set email alerts
|

In silico Study Phytosterol Cymbopogon citratus and Curcuma longa as Inhibitor Agent 3C-Like Protease SARS-CoV-2

Abstract: Background and Objective: Lemongrass (Cymbopogon citratus) and turmeric (Curcuma longa) are widely used by the community for traditional medicinal spices and cooking spices. In the era of the COVID-19 pandemic, people use lemongrass and turmeric to increase immunity and protect the body from infection with the SARS-CoV-2 virus. However, the antiviral mechanisms have not been studied much. This study aims to predict the bioactivity of the phytosterol compounds of lemongrass and turmeric for COVID-19 therapy thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Phytosterols are naturally occurring plant molecules with a structure similar to cholesterol, 70 and they have been demonstrated to possess the antiviral activity of several sterols against the spike protein of the COVID-19 virus and influenza-A virus. 63,71 Our study identified several phytosterols, including β-sitosterol and Δ7-avenasterol, demonstrating potent inhibitory affinity (Figure 3A). Earlier studies have also shown the potential health benefits, including antiviral effects of β-sitosterol, which has been shown to reduce the infectivity of the hepatitis-B virus and HIV, possibly by hindering the attachment of viruses to host cells.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Phytosterols are naturally occurring plant molecules with a structure similar to cholesterol, 70 and they have been demonstrated to possess the antiviral activity of several sterols against the spike protein of the COVID-19 virus and influenza-A virus. 63,71 Our study identified several phytosterols, including β-sitosterol and Δ7-avenasterol, demonstrating potent inhibitory affinity (Figure 3A). Earlier studies have also shown the potential health benefits, including antiviral effects of β-sitosterol, which has been shown to reduce the infectivity of the hepatitis-B virus and HIV, possibly by hindering the attachment of viruses to host cells.…”
Section: Discussionmentioning
confidence: 91%
“…For instance, Sinefungin is a small molecule that has been shown to inhibit the MTase activity of several flaviviruses. 63 However, the study showed a low potency of Sinefungin on NS5 of ZIKV compared to other flaviviruses' MTase domain; additionally, the toxicity associated with the particular drug had raised concern about its use. 64 Hydrogen bonding and hydrophobic interactions are crucial in facilitating significant ligand binding at the active site residues of the receptor in docked complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Phytosterols are naturally occurring plant molecules with a structure similar to cholesterol, 62 and they have been demonstrated to possess antiviral activity of several sterols against the spike protein of the COVID-19 virus and influenza-A virus. 56,63 Our study identified several phytosterols, including β-sitsterol and Δ7-avenasterol, demonstrating potent inhibitory affinity (Figure 3A). Earlier studies have also shown the potential health benefits including antiviral effects of β-sitosterol, which has been shown to reduce the infectivity of the hepatitis-B virus and HIV, possibly by hindering the attachment of viruses to host cells.…”
Section: Discussionmentioning
confidence: 91%
“…For instance, Sinefungin is a small molecule that has been shown to inhibit the MTase activity of several flaviviruses. 56 However, the study showed a low potency of Sinefungin on NS5 of ZIKV compared to other flaviviruses' MTase domain; additionally, the toxicity associated with the particular drug had raised concern about its use. 57 Hydrogen bonding and hydrophobic interactions are crucial in facilitating significant ligand binding at the active site residues of the receptor in docked complexes.…”
Section: Discussionmentioning
confidence: 99%